Influence of Cable Spacing on Flame Interaction and Combustion Characteristics of Parallel Thermoplastic Cables - Rongshui Qin; Xiangxiang Zhang; Yuyao Li; Jinchao Wei; Chao Ding; Yan Jiao (Fire, 2025)
Cable fires pose significant risks to electrical infrastructures, and cable spacing plays a crucial role in influencing fire propagation behaviors. In this study, the combustion characteristics of two parallel thermoplastic cables under varying spacing conditions were systematically investigated through controlled experiments. Key parameters, including flame merging behavior, flame morphology, mass loss rate, flame spread rate, flame temperature, and radiant heat flux, were analyzed. The results revealed that cable spacing critically affects flame interaction, with three distinct flame merging modes—continuous merging, intermittent merging, and non-merging—identified as spacing increases. A critical spacing of 2.5 mm was found, at which the flame spread rate and mass loss rate reached their maximum, approximately 1.7 times higher than that of a single cable. At intermediate spacings (2.5–12.5 mm), enhanced flame interaction and radiative feedback significantly intensified combustion, leading to higher flame temperatures and radiant heat peaks. Conversely, insufficient oxygen supply at zero spacing and reduced flame interaction at large spacings (15 mm) resulted in diminished combustion efficiency. These findings highlight the importance of cable spacing as a key design parameter for mitigating fire hazards in electrical installations, providing valuable insights for fire safety engineering and risk assessment.